Holiday effect di Bursa Efek Indonesia, di Bursa Efek Amerika dan di Bursa Efek Jepang sebelum, sesaat dan sesudah pandemi covid-19 - Apriani, Suci Selia; Komariah, Siti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The phenomenon of traders entering the capital market is one of the causes of the stock market becoming unstable and experiencing market inefficiencies, which are often known as